Developing A Bilingual Guidebook to Improve Visitors’ Experience In Kampoeng Heritage Kajoetangan Malang - Ananda Putri Hardiyanti (UPT P2M Politeknik Negeri Malang, 2021)
Kampoeng Heritage Kajoetangan Malang, a potential home to a tourist magnet in Malang, is an tourismt asset that has not been marketed well. Unfortunately, the local administration and inhabitants have not fully tapped into the area’s prospective revenue streams. The number of visitors is still low. A bilingual guidebook is one of the solutions to improve the number. Based on this background, the objective of the research was to create a bilingual guidebook for Kampoeng Heritage Kajoetangan Malang to improve visitors’ experience.The researcher employed research and development paradigm and used Borg and Gall’s developmental framework to craft a bilingual guidebook (in both Indonesian and English) for Kampoeng Heritage Kajoetangan Malang. Expert evaluations revealed favourable outcomes. Subsequent field trials confirmed the guidebook’s utility, affirming its capacity to improve visitor experiences and provided comprehensive locale-related information.